Establishment of a mouse model of ovarian oxidative stress induced by hydrogen peroxide - Liang, Huili; Wu, Shuaishuai; Zhang, Zhenwei; Khan, Muhammad Zahoor; Zhan, Yandong; Zhu, Mingxia; Wang, Shoushan; Liu, Wenqiang; Wang, Changfa; Cao, Guiling; Han, Ying (Frontiers in Veterinary Science, 2024)
IntroductionOxidative stress, resulting from environmental changes, significantly affects female fertility. Developing a mouse model to study oxidative stress lays the groundwork for research into human reproductive health and livestock fertility.Materials and methodsIn this study, we established and evaluated an oxidative stress model by administering hydrogen peroxide (H2O2) to mice. ICR mice of similar age (7–8 weeks old) and average body weight (31.58 ± 1.12 g) were randomly assigned to four groups (A, B, C, and D). Group A served as the control and was injected with a saline solution, while groups B, C, and D received saline solutions containing 0.75%, 1.50%, and 3.0% H2O2, respectively, over one week. We measured the body weights of all mice before and after the experimental period.Results and discussionOur findings showed that the average body weight of mice in groups A and B increased, while groups C and D experienced weight loss. Group C showed a significantly lower average weight gain compared to groups A and B, and group D exhibited an even more pronounced reduction in weight gain. Although group D had a high mortality rate, there was no significant difference in mortality rates among groups B, C, and D. Serum malondialdehyde (MDA) content increased with higher concentrations of H2O2, with a significant difference noted between groups C and A. Catalase (CAT) activity in group B was significantly higher than in group A, while superoxide dismutase (SOD) activity in group C was notably elevated compared to groups A and B. Conversely, glutathione peroxidase (GSH-Px) activity in group C was significantly lower than in both group A and group B. Hematoxylin and eosin (HE) staining revealed changes in ovarian morphology and follicle dynamics. The percentage of atretic follicles in group C was significantly higher than in the control group, and group D had a significantly lower total number of healthy follicles compared to the untreated group. Increased H2O2 content resulted in a reduction of ovary size and an irregular appearance in group D.ConclusionBased on our findings, treatment with 1.50% H2O2 effectively established an oxidative stress model in mice within 1 week. This model serves as a valuable reference for future clinical studies on oxidative stress and reproductive disorders in female animals and humans.